PENGEMBANGAN BAHAN AJAR MULTIMEDIA INTERAKTIF UNTUK MOTIVASI BELAJAR KELAS IV MIN 3 PONTIANAK - Firniza Fitri; Kartono Kartono; Suhardi Marli (Universitas Tanjungpura, 2020)
Abstract This study aims to describe interactive multimedia teaching materials, analyze the feasibility of interactive multimedia teaching materials, and analyze students' learning motivation levels during the use of interactive multimedia teaching materials in class IV MIN 3 Pontianak students. The research method is Research and Development adapting by Thiagarajan 4D design development model. Data sources of this research are the results of the validation of media experts, the results of the validation of the material experts, the results of students’ responses, and the results of observation during the use of interactive multimedia teaching materials. Observation and documentation questionnaire on the validation process of material experts, media experts, and documentation during the use of the materials by students. The results showed that during the process it through 5 stages namely the preliminary study stage, the define stage, the design stage, the development phase, and the dissemination stage. The feasibility of the materials has the average percentage of aspects of the media by 89% valid category, from the aspect of the material percentage of an average of 88.5% valid categories. Learning motivation of students during the use of the materials for six days has an average percentage of 96% categorized as very good.Keywords: Development, teaching materials, interactive multimedias, motivation